Optimal Release Policies for Software Reliability Growth Model (SRGM) With Maintenance Costs - Jain, Madhu; Maheshwari, Sandhya; Priya, Kriti (Universiti Utara Malaysia Press, 2006)
A component based or module-based software system is considered in which the software reliability growth model (SRGM) follows a mixed distribution. We address the problem of determining the optimal testing time of software so that the total maintenance costs of the software could be minimized and a desired level of reliability could be achieved as well. The total maintenance costs of the software is obtained by assuming a warranty period in the operational phase of the software during which the cost incurred in the maintenance, is paid by the developer. The present value of the money is considered while calculating the total maintenance costs by including a discount rate. A technique for estimating the parameters of the SRGM is also suggested. Numerical illustrations are provided for testing the validity of the analytical results.